The Language Characteristic and Its Acculturation from Chinese Speakers in Losari, Cirebon Regency, West Java: The Acculturation of Chinese with Javanese Culture - Darheni, N (KnE Social Sciences, 2018)
The linguistic situation in Cirebon is diglossic. In Cirebon, a number of languages are spoken, namely Cirebonese, Cirebonese Sundanese, Indonesian, and foreign languages such as Arabic, Chinese, Dutch, and English. Mandarin is one of the languages productively used by the Chinese ethnic group in Losari district, Cirebon (borderland between West Java and Central Java). The acculturation of language and the culture between the Chinese ethnic group and the native group can be seen from the vivid diffusion in the way of thinking and the behavior of both ethnic groups in the region. In addition, the primordialism between the native and Chinese ethnic group is not clearly visible, which indicates the establishment of communication in social, economic, governance, and power aspects. Consequently, the acculturation of Mandarin with Javanese culture in Eastern Cirebon covers phonological, lexical or diction (which is the most frequent), morphological (the most unique), and syntactical aspects. In addition, this paper is the result of a field research using observation, note taking, and interview techniques (directly with the native speakers of the Chinese ethnic group), as well as a literature study. Keywords: acculturation, characteristics of language, Chinese culture, Javanese, linguistic borderland